A Central African “witch-hunt”: bulungo oaths in Massangano (Angola) in 1717: Uma “caça às bruxas” centro-africana: os juramentos do bulungo em Massangano (Angola) em 1717 (Revista de História da UEG (REVHIST), 2022)
This paper discusses a denunciation sent from Massangano, Angola, to the Portuguese Inquisition tribunal of Lisbon in 1717, in which several Africans were charged of witchcraft by their relatives and neighbors. Many of those Africans had been previously subjected to Mbundu divinatory and juridical ceremonies called “bulungo oaths” (“juramentos do bulungo”) in order to determine their guilt. Considering that witchcraft had different meanings to ecclesiastical agents and to Africans (both accusers and accused alike), the paper suggests that Portuguese and African juridical institutions held relations of both complementarity and dispute in that context. Free Africans in territories under Portuguese administration may have used those institutions selectively and strategically in order to solve conflicts over land use rights.Keywords: Bulungo oaths. Witchcraft. Inquisition. Angola. African religions.